The Influence of Formative Tests on the Learning Outcomes of IPAS Students - Sam, Fatmawati; Iwan, Iwan; Petahuddin, Patahuddin (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to compare the learning outcomes of IPAS students using two forms of formative tests, namely written formative tests and oral formative tests, among fifth-grade students at SDN Benteng Jampea No. 56, Kepulauan Selayar. This research employs a quantitative approach with a simple experimental method. The subjects of the study were fifth-grade students. Data collection techniques were carried out thru the administration of two forms of formative tests, observation, and learning outcome tests. Data were analyzed using descriptive and inferential statistical techniques to determine the difference in the impact of the two forms of formative tests on students' learning outcomes. The research results showed that both forms of formative tests had a positive impact on students' IPAS learning outcomes, but the written formative test showed more effective results compared to the oral formative test. This was evident from the difference in the average learning outcomes of students after the implementation of the two forms of tests. In addition, students became more active, motivated, and found it easier to understand the learning material during the learning process. Based on the data analysis results, it was found that there is a significant difference between the use of written formative tests and oral formative tests on the learning outcomes of fifth-grade students in IPAS at SDN Benteng Jampea No. 56, Selayar Islands. Thus, both forms of formative tests can be used as learning evaluation strategies, but written formative tests are more effective in improving the learning outcomes of elementary school students in IPAS.